Art and science of anamnesis - Miguel Moreno Rodríguez (Medisur)
We can affirm that clinical medicine is both a science and an art. Clinics is dedicated to the individual care of patients and anamnesis is usually its first step. When a doctor is interviewing a patient with true professionalism, he is applying his scientific knowledge in order to know the nature of the morbid disorder and he is using rules and conceptions borrowed from art in a close symbiosis. It is considered that the interview or anamnesis has an extraordinary importance in the clinical practice when looking for the diagnosis. Rules and regulations that are necessary for a good interview in order to avoid mistakes are mentioned. The information obtained through this process needs to be immediately taken to the medical record in a clear, precise and readable way.